PENGEMBANGAN INSTRUMEN PENILAIAN ASPEK PSIKOMOTORIK PADA PRAKTIKUM FAKTOR-FAKTOR YANG MEMPENGARUHI LAJU REAKSI KELAS XI IPA SMA NEGERI 3 PONTIANAK - Septian Triadi Syahputra (Jurnal Ilmiah Ar-Razi, 2018)
The aim of this study was to develop the psychomotor assessment instruments on experiment of factors that influence the rate of reaction which is feasible to be used. The development model used in this research was the modification model of 4P development into 3P which is recommended by Thiagarajan that is defining, designing and developing. Data collection techniques used were structured observation and questionnaire. The research instruments used were observation sheet and questionnaire. Initial field trials conducted on six students of class XII IPA 1, involving four observers while the main field trial conducted on 36 students of class XI IPA 1. The researcher involved four observers and one chemistry teacher. The feasibility of the developed psychomotor aspects assessment instrument is based on validity and practical aspects. The results obtained in this study were: (1) the average value of the validity of the psychomotor aspects assessment instrument was 1.00 with very high criteria and (2) the practicality of the psychomotor aspects assessment instrument based on the observers' response of 94.44 with very high criteria and teachers' response 90.27 with very high criteria. Based on the validity and practicality of the psychomotor aspect appraisal instrument the factors affecting the reaction rate are feasible to use